EFFECTS OF ALUMINUM FIBERS ADDITIVE ON THE COMPRESSIVE STRENGTH OF A CONCRETE - Sudirman Indra; Nadya Rachma; Mohammad Erfan; Endro Yuwono; Ratri Andinisari (Journal of Infrastructure Planning and Engineering, 2024)
Utilizing recycled waste as an additional construction material is an innovation that can reduce the negative environmental impacts caused by waste. One of the wastes that can be utilized in this case is aluminum cans. The use of aluminum fiber in concrete mixtures is appropriate since aluminum is resistant to corrosion or rust. This research aims to determine the effect of adding aluminum fiber on the compressive strength of concrete. The aluminum cans were shaved into fibers with dimensions of 2 x 35 mm. The resulting aluminum fiber is then added into the concrete mixture with a percentage of 0%, 0.05%, 0.075%, 0.1%, and 0.125% of the total volume of the test objects. Tests for compressive strength was then carried out after test specimens were aged for 28 days. The test results showed a peak compressive strength of (20.72 ± 0.35) MPa is observed at the addition of 0.05% aluminum fiber relative to the volume of concrete used for testing. A regression analysis was performed based on the relationship between the amount of aluminum fiber additive and the resulting compressive strength. Based on this analysis, the optimum value for aluminum fiber to be added to the concrete is 0.040% of its volume.